الحصانة التنفيذية للدولة في ظل اتفاقية الأمم المتحدة لحصانات الدول وممتلكاتها من الولاية القضائية: دراسة تحليلية مقارنة - سالم فرىود عناد الجنابي
There is no doubt that executing foreign verdicts is no more than satisfactory or compulsory. If satisfactory execution does not raise any problems for the person who has a valid verdict, it follows that the compulsory execution requires a massive effort from that person to execute the verdict. It is also no doubt that executing against the state is unlike that upon a normal person. This is because the state holds immunity against executive procedures through which the problem of the current research arises. The use of this impunity by the state blocks the compulsory execution if it refrains from the satisfactory execution. This use of impunity by the state creates a difficulty which we can potentially refer to as " floating verdicts". These verdicts have no legal value if they do not have other means to be executed. In this thesis, the researcher aims at identifying the executing immunity of the state and identify the state's finances and actions covered by this immunity and finding a solution to execute these verdicts. The analytical and comparative methods are used in this research to analyze the legal tenets of united nations' conventions related to the immunity of the states and comparing it with other national laws and judicial practices for the states under study. The findings of the study revealed that executing immunity is governed by the nature of the state's actions. In other words, this immunity is ruled by the state's finance and actions which have a sovereignty nature. Accordingly, it is possible for the person who has a valid verdict to execute the verdict on non-sovereign properties and finances belonging to the state. Second, there is also another means of executing which is called "diplomatic protection for the state upon its dependents". Finally, the significance of the research resides in finding out solutions which mitigate the sharpness of the state's immunity and contributes to executing verdicts.